Trust in science and solution aversion: Attitudes toward adaptation measures predict flood risk perception. (15th June 2022) - Spaccatini, Federica; Richetin, Juliette; Riva, Paolo; Pancani, Luca; Ariccio, Silvia; Sacchi, Simona
Abstract: The psychological perception of structural measures developed to respond to hydrogeological hazards is pivotal in determining their efficacy. In this regard, alongside the vast psychological literature on mitigation behaviors, there is a lack of research on psychological constraints related to adaptation infrastructures. To fill this gap, we investigated the role of attitudes toward such measures and their antecedents on risk perception. Based on the Solution Aversion Model, Study 1 ( n  = 194) showed that the more participants oppose the adaptation measures, the less they perceive the risk of flooding. Extending Study 1, Study 2 ( n  = 95) provided evidence that distrust in science predicts people's dislike and aversion toward adaptive measures, which in turn predicts the perception of hydrogeological risk. Finally, Study 3 ( n  = 250) revealed that for participants with a lower level of prior knowledge about adaptation measures, the lack of trust in science predicts more negative attitudes toward adaptation, which is associated with lower risk perception. Highlights: Attitudes toward adaptation are positively associated with perceived flood risk. Distrust in science predicts dislike and aversion toward adaptation measures. When knowledge is scarce, trust in science indirectly affects perceived flood risk. Trust in science, being a psychological motivation, impacts environmental cognition. The aversion toward the problem solutions motivates disbelief about environmental risk.